2008
DOI: 10.1007/s11695-007-9399-1
|View full text |Cite
|
Sign up to set email alerts
|

Is Preoperative Manometry in Restrictive Bariatric Procedures Necessary?

Abstract: Preoperative esophageal manometry is advised for restrictive procedures such as AGB and SG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 25 publications
2
38
0
4
Order By: Relevance
“…Suter et al [17] found that abnormal pH monitoring predicted overall long-term complications, especially food intolerance and pouch dilation and that a high pressure of the lower esophageal sphincter was related to long-term food intolerance. Consistent with this, Klaus and Weiss [18] stated recently that preoperative esophageal manometry is advised for restrictive procedures such as LAGB because functional disorders of the esophageal body and the lower esophageal sphincter can be identified before surgery. As a consequence, LAGB should not be considered a therapeutic option for patients with weak esophageal body motility because esophageal dilation, esophageal stasis, and consequent esophagitis could occur during long-term follow-up evaluation, and band deflation would be inevitable.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Suter et al [17] found that abnormal pH monitoring predicted overall long-term complications, especially food intolerance and pouch dilation and that a high pressure of the lower esophageal sphincter was related to long-term food intolerance. Consistent with this, Klaus and Weiss [18] stated recently that preoperative esophageal manometry is advised for restrictive procedures such as LAGB because functional disorders of the esophageal body and the lower esophageal sphincter can be identified before surgery. As a consequence, LAGB should not be considered a therapeutic option for patients with weak esophageal body motility because esophageal dilation, esophageal stasis, and consequent esophagitis could occur during long-term follow-up evaluation, and band deflation would be inevitable.…”
Section: Discussionmentioning
confidence: 75%
“…The current literature suggests an association between the function of the upper digestive tract and long-term complications after LAGB [17,18]. We analyzed the potential impact of preoperative upper gastrointestinal (GI) testing on outcome after LAGB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine preoperative esophageal manometry has been advocated by some authors [8,9], in order to detect esophageal motility disorders that could influence the outcomes after bariatric surgery. However, this systematic preoperative esophageal testing should be recommended only if it could predict these complications and assist the choice of another type of bariatric surgery less prone to induce them.…”
mentioning
confidence: 99%
“…Postoperative emesis was more frequent in patients with abnormal manometry findings, but was managed medically as effectively as in the group with normal manometry. Klaus and Weiss [8] advocated the use of preoperative manometry before gastric banding: they proposed that low amplitude of distal esophageal contractions and low LES pressure are contraindications for gastric banding, but their data are not definitely convincing, as they did not show that postoperative dysphagia occurred more frequently in patients with preoperative esophageal dyskinesia. Similarly, Merrouche et al [11] found 5 patients with postoperative esophageal ''dyskinesia'' among a cohort of 60 gastric banding, 2 out of 5 with ''pseudo-achalasia'' manometric findings: all these 5 patients had a normal esophageal manometry before surgery.…”
mentioning
confidence: 99%